Audit Committee Financial Experts: Leveraging Their Information Advantage in Accounting, Auditing, and Corporate Governance - Zachery (Ziqi) Ma; Linna Shi; Katherine (Kexin) Yu; Nan Zhou (Encyclopedia, 2025)
To enhance financial reporting quality through increased oversight, the Sarbanes–Oxley Act (SOX) Section 407 mandates that firms disclose whether their audit committee includes a financial expert or explains the absence of such an expert. The definition of a financial expert has been broadened to encompass not only accounting knowledge but also finance or supervisory experience. Financial experts on audit committees possess an advantage in information access due to their role on the committee and an advantage in information processing because of their superior skills. This combination of skills and access to private information enables audit committee financial experts to achieve superior performance. We review articles that show audit committee financial experts leveraging their information advantage in accounting to improve financial transparency, in auditing to maintain audit integrity, and in corporate governance to enhance monitoring effectiveness.